Implementation of Human Resource Development in Improving The Skills and Competitive Capabilities of Employees on PT. BPR Rohil from The Perspective of Maqasid Al-Syari’ah Abu Yusuf - Amrin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study aims to analyze the implementation of Human Resources (HR) development in improving the skills and competencies of PT. BPR Rohil employees through the perspective of Maqasid al-Syari'ah Abu Yusuf. The rapid development of Islamic financial institutions demands quality and competitive HR. This study uses a descriptive qualitative method with interview techniques, observation, and documentation of the management and employees of PT. BPR Rohil. The results show that HR development has been implemented through training, continuing education, and competency improvement based on sharia principles. The perspective of Maqasid al-Syari'ah Abu Yusuf emphasizes that HR development does not only focus on improving technical capabilities, but also on the formation of Islamic character, moral values, and employee welfare. This study recommends the development of HR based on maqasid al-syari'ah through four main pillars, namely technical competence, Islamic character, leadership, and welfare, which are carried out in stages and continuously evaluated to support Islamic economic goals.